2016
DOI: 10.1016/j.cortex.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal interactions during non-linguistic auditory processing in cochlear-implanted deaf patients

Abstract: Due to signal distortion, speech comprehension in cochlear-implanted (CI) patients relies strongly on visual information, a compensatory strategy supported by important cortical crossmodal reorganisations. Though crossmodal interactions are evident for speech processing, it is unclear whether a visual influence is observed in CI patients during non-linguistic visual-auditory processing, such as face-voice interactions, which are important in social communication. We analyse and compare visual-auditory interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 75 publications
1
9
1
Order By: Relevance
“…The participants were not diagnosed with psychiatric or neurological disorders, as assessed by a short questionnaire at inclusion in the study. The control participants were selected for their hearing-in-quiet capacities rather than their age, leading to age differences between the groups [ 20 , 69 , 90 ]. As age-difference could have played a role in the CI results, we performed Pearson correlations between each score obtained in the Results section and the age of the CI users, with Bonferroni correction for multiple testing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were not diagnosed with psychiatric or neurological disorders, as assessed by a short questionnaire at inclusion in the study. The control participants were selected for their hearing-in-quiet capacities rather than their age, leading to age differences between the groups [ 20 , 69 , 90 ]. As age-difference could have played a role in the CI results, we performed Pearson correlations between each score obtained in the Results section and the age of the CI users, with Bonferroni correction for multiple testing.…”
Section: Methodsmentioning
confidence: 99%
“…This audiovisual enhancement is more efficient in CI users compared to NH participants for all types of speech, even foreign-accented speech [ 68 ]. One study on non-linguistic speech processing, using voice gender identification, suggested that CI users are influenced more strongly by visual information than are NH participants, even for tasks not directly related to speech comprehension [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these tokens were produced naturally and used as stimuli in their natural form (n = 29), while other studies used synthetic or synthesized speech (n = 8). For example, Barone et al (2016) recorded two voices (one female and one male) producing a word, and using a specialized speech manipulation software, they morphed these two voices to a continuum of 11 voices, ranging from 100% female to 100% male and 9 gender-interpolated voices in between.…”
Section: Task Characteristicsmentioning
confidence: 99%
“…Other studies found significant differences between groups in the manner by which listeners encoded vocal properties (see Section 3.5; Barone et al, 2016;Kovačić & Balaban, 2009;Meister et al, 2016;Zaltz et al, 2018). Another study examined whether topdown information, such as visual information, would influence listeners' gender rating of voices (Barone et al, 2016).…”
Section: Comparison To Individuals With Typical Hearingmentioning
confidence: 99%
See 1 more Smart Citation